2012
DOI: 10.1007/s00421-012-2455-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue is specific to working muscles: no cross-over with single-leg cycling in trained cyclists

Abstract: Fatigue induced via a maximal isometric contraction of a single-limb muscle group can evoke a “cross-over” of fatigue that reduces voluntary muscle activation and maximum isometric force in the rested contralateral homologous muscle group. We asked whether a cross-over of fatigue also occurs when fatigue is induced via high-intensity endurance exercise involving a substantial muscle mass. Specifically, we used high-intensity single-leg cycling to induce fatigue and evaluated associated effects on maximum cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
3
23
2
5
Order By: Relevance
“…In the literature, crossover fatigue effects have been observed as a decrease in voluntary muscle activation (Rattey et al 2006), force (Martin and Rattey 2007) and an increase in postural sway (Paillard et al 2010) of the contralateral non-fatigued limb. The findings of the present study are similar to published studies that have found no evidence of crossover force deficits associated with unilateral fatigue (Zijdewind et al 1998;Grabiner and Owings 1999;Todd et al 2003;Regueme et al 2007;Strang et al 2009;Place et al 2004;Ross et al 2007Ross et al , 2010Elmer et al 2013). The study by Zijdewind et al (1998) used a similar protocol with 30 % MVICs regularly interrupted with MVICs and brief rest periods in the right first dorsal interosseus muscle until failure and found no evidence of crossover force deficits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the literature, crossover fatigue effects have been observed as a decrease in voluntary muscle activation (Rattey et al 2006), force (Martin and Rattey 2007) and an increase in postural sway (Paillard et al 2010) of the contralateral non-fatigued limb. The findings of the present study are similar to published studies that have found no evidence of crossover force deficits associated with unilateral fatigue (Zijdewind et al 1998;Grabiner and Owings 1999;Todd et al 2003;Regueme et al 2007;Strang et al 2009;Place et al 2004;Ross et al 2007Ross et al , 2010Elmer et al 2013). The study by Zijdewind et al (1998) used a similar protocol with 30 % MVICs regularly interrupted with MVICs and brief rest periods in the right first dorsal interosseus muscle until failure and found no evidence of crossover force deficits.…”
Section: Discussionsupporting
confidence: 92%
“…This crossover or non-local fatigue effect has been identified for upper (Humphry et al 2004;Halperin et al 2014a, b) and lower limbs (Rattey et al 2006;Martin and Rattey 2007;McLean and Samorezov 2009;Paillard et al 2010;Halperin et al 2014a, b). Despite this evidence of crossover fatigue, controversy about its existence remains with many studies being unable to confirm its occurrence (Zijdewind et al 1998;Grabiner and Owings 1999;Todd et al 2003;Regueme et al 2007;Strang et al 2009;Place et al 2004;Ross et al 2007Ross et al , 2010Elmer et al 2013;Halperin et al 2014a, b). Hence there is a conflict in the literature that needs further exploration.…”
Section: Introductionmentioning
confidence: 95%
“…E + S also showed unchanged and S + E increased maximum EMG after 24 weeks during maximal isometric muscle actions. A high correlation (p < 0.001, r = 0.83) between the individual changes in voluntary activation and maximal knee extension force was found for E + S during weeks [13][14][15][16][17][18][19][20][21][22][23][24]. Neural adaptations showed indications of being compromised and highly individual relating to changes in isometric strength when E + S-training was performed, while gains in one-repetition maximum, endurance performance and hypertrophy did not differ between the training modes.…”
mentioning
confidence: 65%
“…Possible residual fatigue from a cycling endurance loading could be expected to compromise the quality of a subsequent lower-body strength loading session, as it is known that the quadriceps femoris muscle group contributes to continuous cycling with a significant percentage of its maximum activity even at relatively low workloads [19]. Additionally, impairments in maximal voluntary neuromuscular function following fatiguing cycling appear to be specific to the working muscles [18], and prolonged cycling exercise appears to limit the force-generating capacity to the muscles via both central and peripheral mechanisms, thus leading to a reduction in muscular capacity in the working muscles during subsequent activities [2,18,33]. Further clarification is needed as to whether fatigue-induced neural responses from the endurance component alone through inhibitory mechanisms can be regarded as responsible for disadvantageous neural adaptations following the present E + S training program, or whether the immediate addition of a strength-loading is the factor overloading the nervous system.…”
mentioning
confidence: 97%
“…Todd et al (2003) showed that a sustained elbow flexor MVC was not affected by a previous sustained MVC with the contralateral elbow flexors. Finally, it was repeatedly found that extended aerobic activity such as cycling and marathon runs did not affect grip force, despite significant decrements in force and power production, as well as central activation with the lower limbs (Elmer et al 2013;Millet et al 2003;Place et al 2004;Ross et al 2010). Hence these conflicting results emphasize the need for further investigations.…”
Section: Introductionmentioning
confidence: 84%